Point‐of‐Care Diagnostics: Multiplexed Luminescence Oxygen Channeling Immunoassay Based on Dual‐Functional Barcodes with a Host–Guest Structure: A Facile and Robust Suspension Array Platform (Small 17/2020). Issue 17 (28th April 2020) - Guo, Qingsheng; Wang, Yao; Chen, Cang; Wei, Dan; Fu, Jianping; Xu, Hong; Gu, Hongchen
Abstract : In article number 1907521, Hong Xu, Hongchen Gu, and co‐workers present a suspension array platform that combines barcode technology and a luminescent oxygen channeling immunoassay. A unique dual‐functional barcode based on a host‐guest structure is constructed as the microcarrier to facilitate multiplexed detection with simple "mix‐and‐measure" operability. This work provides an ideal platform for the development of point‐of‐care diagnostics.